﻿Geographic differentiation in male calling song of Isophya modestior (Orthoptera, Tettigoniidae, Phaneropterinae) - Slobodan Ivković; Dragan Chobanov; Laslo Horvat; Ionuț Ștefan Iorgu; Axel Hochkirch (ZooKeys, 2022)
We studied the songs and morphology of the stridulatory file of Isophya modestior across its complete geographic range, in order to test our hypothesis that the male calling song of the species shows strong differentiation between the northern (Pannonian) and southern (Balkan) parts of its distribution range, reflecting its disjunct distribution. Our analyses confirm this hypothesis, separating analyzed specimens of I. modestior into two main groups - one present in the central part of the Balkan Peninsula (representing Isophya modestior sensu stricto), with the second group occurring in the Pannonian Basin, Dinarides, Slovenia and NE Italy. The most reliable difference between the groups is the duration of the main syllable, the number of stridulatory teeth and number of pulses in the main syllable, where all values are higher in specimens from the Balkan Peninsula. Additional analyses showed that within the second group, there are differences in analyzed characters between specimens from the Pannonian Basin and specimens from the Dinaric area, the latter ones having intermediate song characteristics, closer to the group from the Balkan Peninsula. Our study shows that detailed bioacoustic analyses can help to unravel patterns of intraspecific differentiation and thus provide a useful tool for taxonomic studies.